MENINGKATKAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN MELUKIS DARI BAHAN BEKAS - AL Maidah, Suherman, Yayah Rukhiyah (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
This research aims to determine the use of used materials on the creativity of children aged 5-6 years. This research was conducted on the basis of problems that emerged in PAUD Ar-rasyidin, Cikande District in the 2023-2024 academic year. The results of observations in the field show that problems occur due to children's lack of creativity in carrying out painting activities, lack of techniques in learning so that they do not stimulate children to create their own ideas according to their imagination. implemented from February to June 2024. The subjects of this research were 17 children aged 5-6 years in group B. Consisting of 10 boys and 7 girls, the aims of this research are as follows: (1) To find out the imaginative condition of creative abilities through painting activities in group B, (2) To have high curiosity. Painting from used materials can increase creativity, (3) Confidence (4) Dare to take risks (5) Independence in thinking. The method used is Classroom Action Research (PTK) which refers to Kemmis and McTaggar, its implementation consists of 2 cycles using 4 action research components, namely planning, action, observation and reflection. The results of the research that has been carried out show that the activity of learning to paint used materials increases children's creative abilities, as evidenced by an increase in creativity in each cycle. In the pre-research the average ability of children was 43.67%, after being given action in cycle I there was an increase with an average of 73.71%, this shows that there was an increase in children's ability on average of 30.04%. Based on these data, it is said that this research has not met the criteria for success, so the researchers took action in cycle II. The results of cycle II data obtained data on increasing creativity through painting activities from used materials in children aged 5-6 years, an average increase of 90.3%. then there was an increase from cycle I to cycle II of 16.59%.